PENGARUH INSENTIF PAJAK DAN EDUKASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KABUPATEN ENREKANG - Miftahuddin; Amran; Endang Winarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the positive contribution of tax incentives and tax education on the tax compliance of MSME taxpayers in Enrekang Regency. The sampling technique used in this study was simple random sampling, resulting in 104 samples. The method used was quantitative statistical method, and data were collected through interviews, questionnaire distribution (direct and online), and literature review to obtain research data. The data were analyzed using multiple linear regression analysis with SPSS version 29. The results show that the Tax Incentive variable has a positive and significant effect on the compliance of MSME taxpayers in fulfilling their obligations. Conversely, the Tax Education variable does not have a positive and significant effect on the compliance of MSME taxpayers registered with the Enrekang KP2KP.